Об одной задаче с начальными данными для волнового уравнения - Есенбаева, Г.А. (Изд-во КарГУ, 2011)
Мақалада берілген бастапқы шарттарымен бір толқынды теңдеу үшін есеп қарастырылады. Ол есеп екі тəсілмен зерттеледі: бірінші жағдайда есептің аналитикалық шешімі Риман функциясының көмегімен құрылған, ал екіншіде — Лапластың интегралдық түрлендіруін қолдану арқылы алынған. Екі əдісті қолдану барысында кездескен қиыншылықтарға қарамастан, тиімді екендігі дəлелденген. In the given article one problem with the initial conditions for the wave equation has been considered. The study problem has been investigated in two difference ways. In the first case the analytical solution of this problem with the initial conditions for the wave equation has been built by means of the Remain function. In the second case the analytical solution of the more common problem for this wave equation has been obtained with the application of integral transformation of Laplace. The conclusion has been made that use of this methods is effective and convenient despite of some disadvantages.
About one problem with the initial conditions for the wave equation